HUBUNGAN POSTUR KERJA DENGAN KELELAHAN KERJA PADA AKTIVITAS PENGAMPLASAN BAGIAN FINISHING PT EBAKO NUSANTARA SEMARANG - Tiara Tidy; Baju Widjasena; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Fatigue is a body protection mechanism so that body will be spared from further damage until recovery occurs after the rest. Work posture is a description about body, head and limb position. Incompatibility work posture will cause fatigue and grievance which lead to work accident. The purpose of this research was to analyze the correlation of work posture with fatigue in sanding activity of finishing section at PT. Ebako Nusantara Semarang. This was an analytical observational study with cross sectional design. Total samples of the research were 26 workers. Work posture was measured using REBA and fatigue was measured using DLRT. Data was analyzed using Fisher Probability Exact Test. The results showed that majority of the respondents were having fatigue (69.2%). The 88.5% workers were having whole work postures scores in moderate category. Statistical analysis results showed that there were correlations of whole work postures (p= 0.02), back posture (p=0.02), and neck posture (p= 0.01) with fatigue and there were no correlations of legs posture (p=0.38), upper arm posture (p=0.67), forearm posture (p=1.00) and wrist posture (p=0.09) with fatigue in sanding activity of finishing section at PT. Ebako Nusantara Semarang. It was suggested for the company to use wheeled work desk to elevate the work field of the object that would be sanded, so the workers did not have to bend over. Workers were recommended to do stretching before working, when the body felt tired, on the sidelines of the work and changed the body position periodically when reached out the surface side of the sanded object.